KILO WATT HOUR RECORDING SYSTEM PT.TRIMITRA MEDIUM ON USING SAKTI BORLAND DELPHI 6.0 - Aswandi Kurniadi; Sunarto Sunarto, SSi, MMSI (Jurnal Sistem Informasi, 2003)
In the economic growth, education and the rapid growth of technology, computer technology can simplify and satisfactory service to consumers in the application of recording meters using the computer. For that needed the help of computers in the p iping system to input data fast and accurately. With the help of a computer anyway, we can open a new nuance in inputting the information storage reporting to customers that will be printed as a report to the CEO.Â  Users kwh meter recording system, via a co mputer that is available, can be directly input the data using a program that has been available for ease in inputting data and more quickly and accurately. Computers can search the keyword information and to provide some qualified answers. To further the user can select appropriate answers with a question.Â  This book's information system is expected to attract consumer attention to be come, buy and subscribe to the book, and free time can be used to book officer can maintain the quality and quantity of books being sold